Collaborative professional learning: cultivating science teacher leaders through vertical communities of practice. Issue 3 (27th May 2019) - Trabona, Kristen; Taylor, Monica; Klein, Emily J.; Munakata, Mika; Rahman, Zareen
ABSTRACT: This article presents findings from a multi-year study of a grant-funded professional development fellowship program that supports teachers in becoming science teacher leaders and improving science curriculum and instruction. The program's activities are designed to: (1) create and support a corps of teacher leaders, (2) institute a culture reflective instruction, and (3) improve teacher quality through vertical articulation of curriculum and professional development. This paper shares the experiences of fellows in our third cohort during their first year in the program and focuses on their collaboration in a vertical group. Three significant themes emerged in the data: tendency to participate in a pseudo community (engaging in superficial conversation); focus on emerging problems of practice; and finally, interactions that encourage pulling back the curtain and reflecting on the details of practice.